Increased Maternal BMI at Time of Delivery Associated with Poor Maternal and Neonatal Outcomes - Steffen, Haley A.; Swartz, Samantha R.; Kenne, Kimberly A.; Wendt, Linder H.; Jackson, J. Brooks; Rysavy, Mary B. (American Journal of Perinatology, 2024)
Objective Current literature on the risks and outcomes of obesity in pregnancy almost exclusively utilizes prepregnancy body mass index (BMI). Given the rising obesity rate across the United States along with a paucity of available information on the relationship between delivery BMI and maternal and neonatal outcomes, our study aimed to determine the association of maternal BMI at delivery with antepartum, intrapartum, and neonatal complications at an academic referral hospital.Study Design This study is a secondary analysis of data collected for a prospective cohort study of Coronavirus Disease-2019 (COVID-19) in pregnancy. This analysis included all patients who delivered term singleton infants between May 1, 2020, and April 30, 2021, at the University of Iowa Hospitals and Clinics. Demographic and clinical data were obtained from the electronic medical record. The relationship between maternal BMI and maternal and neonatal characteristics of interest was assessed using logistic regression models. A statistical significance threshold of 0.05 was used for all comparisons.Results There were 1,996 women who delivered term singleton infants during the study period. The median BMI at delivery was 31.7 kg/m2 (interquartile range: 27.9, 37.2), with 61.1% of women having a BMI ≥ 30.0 kg/m2. Increasing BMI was significantly associated with nonreassuring fetal status, unscheduled cesarean birth, overall cesarean birth rate, postpartum hemorrhage, prolonged postpartum stay, hypertensive diseases of pregnancy, neonatal hypoglycemia, neonatal intensive care unit admission, decreased APGAR score at 1 minute, and increasing neonatal birth weight. Even when controlling for preexisting hypertension in a multivariate model, increasing BMI was associated with gestational hypertension and preeclampsia.Conclusion Increased maternal BMI at delivery was associated with adverse perinatal outcomes. These findings have implications for clinical counseling regarding risks of pregnancy and delivery for overweight and obese patients and may help inform future studies to improve safety, especially by examining reasons for high cesarean rates.Key Points
Keywords: pregnancy outcomes; obstetric delivery; body mass index; cesarean delivery; neonatal intensive care